Fate of Ice Nucleation-Active Pseudomonas syringae Strains in Alpine Soils and Waters and in Synthetic Snow Samples - Goodnow, R. A. (1990)
The stability of the ice nucleation activity (INA) and viability of INA Pseudomonas syringae 31a, used as an ice nucleator in the manufacture of synthetic snow, was determined in snow. The viability of P. syringae 1-2b, a rifampin-resistant mutant selected from strain 31a to improve recovery from test samples, was determined in laboratory tests of three alpine soil and water samples from three different sources. Snow samples were exposed to environmental conditions or held in darkness at −20°C. Samples of soil and water were maintained in darkness at 0, 7.5, or 15°C. Parent strain 31a INA decreased significantly (>99.0%) in snow exposed to sunlight and freeze-thaw, while the INA of the cell population in snow held in darkness at −20°C remained essentially unchanged. No viable strain 31a was detected in snow exposed to the environment after 7 days, while the viability of strain 31a in snow held in darkness at −20°C decreased to <3% of the original inoculation at the test conclusion. Mutant strain 1-2b viability was undetectable or had decreased significantly 19 days postinoculation in soil samples held at 0 or 15°C. In contrast, 1-2b viability remained detectable at low levels for the duration of the test in soils held at 7.5°C. The 1-2b population demonstrated a significantly longer half-life in peatlike soil than in the loam soils tested. The rate of decrease in 1-2b viability was essentially the same in the three alpine water samples tested with respect to water temperature and sample location.